Association of Caveolin-1 Expression With Prostate Cancer: A Systematic Review and Meta-Analysis - Chen, Pei; Zhang, Yu-ling; Xue, Bai; Xu, Guo-ying (Frontiers in Oncology, 2021)
Purpose: The prognostic role of caveolin-1 in prostate cancer remains inconclusive. Our meta-analysis was performed to evaluate the prognostic value of caveolin-1 in prostate cancer and ascertain the relationship between caveolin-1 expression and clinicopathologic characteristics in prostate patients. Methods: Databases were used to retrieve the published studies about caveolin-1 expression and prostate cancer. After studies searching, data extraction, the meta-analysis was carried out by Review manager 5.3 software. Odds ratio (OR) with 95% confidence interval (CI) was selected to estimate the pooled effect. Funnel plot was used to assess publication bias. Results: A total of 9 studies were collected, including 859 cases of prostate cancer, 72 cases of high-grade intraepithelial neoplasia (HGPIN) and 157 cases of normal control. Results of meta-analysis showed that the positive rate of caveolin-1 expression in prostate cancer was 18.28 times higher than that in normal control (OR = 18.28, 95% CI: 9.02-37.04, P<0.01), 4.73 times higher than that in HGPIN, (OR= 4.73, 95% CI: 2.38-9.42, P<0.01). The relationship between caveolin-1 and clinicopathological characteristics of prostate cancer showed that: the caveolin-1 in (PSA >10 vs ≤ 10) (OR=2.09, 95% CI: 1.35-3.22, P<0.01), differentiation degree (low) vs (medium, high) (OR = 2.74, 95% CI: 1.84-4.08, P < 0.01), TNM stage (T3+T4) vs (T1+T2) (OR =2.77, 95% CI: 1.78, 4.29, P<0.01), lymph node metastasis (with vs without) (OR = 3.91, 95%CI: 2.36-6.48, P<0.01) were statistically significant. Conclusion: Caveolin-1 is overexpressed in prostate cancer, and the overexpression of caveolin-1 can be served as a risk factor and adverse clinicopathological feature of prostate cancer.